MOTIVASI BELAJAR SISWA KELAS 4 SD MUHAMMADIYAH 3 SURABAYA PADA PELAKSANAAN PERTEMUAN TATAP MUKA (PTM ) TERBATAS - Dwi Ulfa Aprelia; Fajar Setiawan; Lilik Binti Minarwati (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
Abstract The purpose of this study was to determine the learning motivation of grade 4 students in the implementation of face-to-face learning (PTM) in a limited manner at SD Muhammadiyah 3 Surabaya. The method used in this research is qualitative method. Data collection techniques using observation techniques, interviews and documentation. The subject of this research is the fourth grade teacher at SD Muahmmadiyah 3 Surabaya. Data based on research results show that distance learning or online has an effect on students' learning motivation. This is because students become bored easily, lack discipline and lack socialization during the distance learning process. Less interesting learning is not like face-to-face learning in class. Therefore, with the limited face-to-face meeting (PTM) learning plan, the spirit of student learning motivation increases. The way to grow student learning motivation can be done by providing learning motivation to students with positive words and building a comfortable, safe, calm learning atmosphere and paying attention to students when limited face-to-face meeting (PTM) learning takes place. Keywords: Motivation to learn; Face-to-face Meeting (PTM).